1987
DOI: 10.1007/bf00007576
|View full text |Cite
|
Sign up to set email alerts
|

The possibility of predator avoidance by Lake Michigan zooplankton

Abstract: Low densities of Diaptomus ashlandi, Diacyclops thomasi, and Daphnia galeata mendotae were measured at depths where Mysis relicta formed nighttime aggregations . Calculations suggest that mysid predation can not account for the rarity of prey animals at these depths, which further suggests that the prey avoided the mysids . Unlike D. galeata mendotae, Daphnia pulicaria was common in mysid aggregations . The somewhat larger size of D. pulicaria may reduce its vulnerability to mysid predation, and consequently m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Spatial overlap of L. macrurus with the DCL has been seen in Lake Michigan, where midnight population maxima of L. macrurus corresponded closely with a marked DCL in August 1999, although the majority of individuals were well below the DCL at other times of day (Barbiero et al, 2005). Schulze and Brooks (1987) also found positive correlations between L. macrurus and deep chlorophyll concentrations in Lake Michigan during July, though apparently not in August. Interestingly, the only other crustaceans to show a positive correlation with deep chlorophyll in that study were copepod nauplii, which suggests the potential continued importance of carnivory throughout the stratified period.…”
Section: Discussionmentioning
confidence: 69%
“…Spatial overlap of L. macrurus with the DCL has been seen in Lake Michigan, where midnight population maxima of L. macrurus corresponded closely with a marked DCL in August 1999, although the majority of individuals were well below the DCL at other times of day (Barbiero et al, 2005). Schulze and Brooks (1987) also found positive correlations between L. macrurus and deep chlorophyll concentrations in Lake Michigan during July, though apparently not in August. Interestingly, the only other crustaceans to show a positive correlation with deep chlorophyll in that study were copepod nauplii, which suggests the potential continued importance of carnivory throughout the stratified period.…”
Section: Discussionmentioning
confidence: 69%
“…Although we focused our study on a single zooplankton species, migration has been observed for Lake Michigan populations of Daphnia pulicaria, Daphnia retrocurva, Bosmina longirostris, Diacyclops thomasi, and Leptodiaptomus spp. (Wells, 1960;Dorazio et al, 1987;Schulze and Brooks, 1987;Barbiero et al, 2000). Our results and similar migration-related temperature effects on the growth of cyclopoid copepods (Makino et al, 2003) and calanoid copepods (Williamson et al, 1996) found in other oligotrophic lakes suggest that vertical migration may be generally important to the growth of migratory zooplankton in Lake Michigan.…”
Section: Discussionmentioning
confidence: 91%
“…Doing this may require depth-stratified sampling of zooplankton, as described in a previous study (Kuns and Sprules, 2000), that is carried out several times over 24-hour periods. Further, variable environmental factors such as predator densities can affect the magnitude of vertical migration in the Great Lakes (Schulze and Brooks, 1987;Pangle and Peacor, 2006;Pangle et al, 2007); thus, sampling at different times of year may be necessary to account for this variation. While such a sampling approach is more laborious than those often used for zooplankton, the potentially-large improvements to the accuracy of zooplankton production estimates are likely worthwhile, particularly given the importance of zooplankton to the Great Lakes ecosystem (Scavia et al, 1986;Miller et al, 1990;Makarewicz et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) . Similarly, Melville & Maly (1981) found that vulnerable prey tended to show a lower degree of overlap in vertical distribution than less vulnerable prey with the predator Chaoborus americanus, as did Schulze & Brooks (1987) with the predator Mysis relicta . In addition, the latter authors concluded that the low degree of overlap between vulnerable prey and the predator was not directly due to cropping effects by the latter .…”
Section: -19 Junementioning
confidence: 99%